Changes in the Regional Differences of the Health State in Hungary after 1989 - Kiss, Eva (National Geographical Journal of India, 2022)
In the state of health there are considerable regional differences within countries owing to complex interaction of numerous factors. According to the survey of UN these differences are more important, because very often they mean sharp spatial differences. In the postsocialist countries including Hungary radical political, economic and social changes have taken place after 1989 which have had a great impact on the state of health too. The main aim of this study is to reveal the changes in the regional differences of the health state of the Hungarian population. The basic question is how the geography of the area with good and bad health changed during the last decades. Based upon the available statistical data at three different times some major health indicators are analysed at regional level after 1989. Illustrations indicate spectacularly the changes regional differences. When analysing them, it turned out that the regional differences in the state of health of the Hungarian population were generally intensifying, and that the spatial pattern of areas with favourable or unfavourable state of health had been also modified during the last 25 years. It has also become obvious that the regional differences are persistent and they are partly determined by inherited regional differences.